Impacto econômico da eficiência energética aplicada a um edifício residencial em Maceió, AL - Accioly, Bruna Melo Patury (2013)
The increasing energy consumption per capita and the impacts on resource consumption for their generation have affected all countries. It is known that the buildings now represent around 40% of the primary energy consumed in the world. In Brazil the residential buildings sector accounts for 23.9% of consumption. Energy efficiency can be adopted in the design of buildings to avoid wastage without compromising the environmental conditions suitable for user comfort. In the years 2009 and 2010 the Technical Regulation on Quality Level Energy Efficiency of Commercial Buildings, and Public Services (RTQ-C) and Regulation of Residential Buildings (RTQ-R) were approved. The regulations establish a rating for the level of energy efficiency of buildings in order to get the Label National Energy Conservation (ENCE). The levels of efficiency varies from A (more efficient) to E (less efficiently).The objective of this dissertation is to evaluate the increase in construction costs of a residential building in Maceió, considering energy conservation measures applied to the envelope as well as the viability of the investment. The methodology adopted was a documentary research for the definition of a residential building that constituted a landmark study and the prescriptive method of RTQ-R to assess its level of energy efficiency. Based on bioclimatic strategies recommended to the city of Maceió, modifications for energy conservation are proposed and evaluated. Those that more increased the efficiency level of the building were incorporated into the original design, resulting in "case 4" with "A" level of energy efficiency, even with a heating system water level "D". The proposed changes in the envelope were quantified and adjusted in the budget worksheet the building in order to find the initial investment required for its implementation. The annual consumption of energy was obtained through computer simulations using the software EnergyPlus. Calculations were made of Period Return (Pay back) and Cost of Conserved Energy (CEC), which are indicators of cost analysis. Considering the constructive characteristics of residential buildings in the city of Maceió, it is concluded that there is an increase in construction costs. However, such an investment is considered advantageous because it represents only 1.2% of the original budget, considered low value and easily absorbed by the housing market. Moreover, the cost indicators showed the feasibility of investment in all simulated scenarios, since in addition to raise the rating to "A" level, the changes adopted in the project provided considerable energy savings to the building. Accordingly, the regulation for labeling of buildings has a positive effect, in that it allows the consumer to choose more efficient solutions, especially at a time when society is assimilating be a limit exploitation of energy resources, as well as the environmental, social and economic exploitation that this may cause.